Particular Effect Of Leadership Style, Work Environment, And Motivation On Employee Performance Of During The Covid-19 Pandemic - Fauzan Dahlan; Setyo Riyanto (Publisher Cv. Inara, 2021)
This study aims to determine how much influence leadership style, work environment, and motivation have on the performance of PT. Djaya Sinar Propertindo employees during The Covid-19 pandemic. The population in this study amounted to 100 people, while in determining the sample used The Slovin's Formula with a 5% sample which obtained a sample of 80 employees. This research was conducted from November 2020 to April 2021. The data were collected using quantitative methods and the analysis used was the data instrument test, classical assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing using SPSS v.25 for windows. Based on the study results, it can be concluded that: hypothesis testing, The F-count is 34,636. In comparison, The F-table is 2.72, which means F-count > F-table. This result shows that Ho is rejected and Ha is accepted. The result means that leadership style, work environment, and motivation simultaneously significantly affect employee performance at PT. Djaya Sinar Propertindo.